Risk - Skinns, Layla; Scott, Michael; Cox, Tony (Cambridge : Cambridge University Press, 2011)
Recent events from the economic downturn to climate change mean that there has never been a better time to be thinking about and trying to better understand the concept of risk. In this book, prominent and eminent speakers from fields as diverse as statistics to classics, neuroscience to criminology, politics to astronomy, as well as speakers embedded in the media and in government, have put their ideas down on paper in a series of essays that broaden our understanding of the meaning of risk. The essays come from the prestigious Darwin College Lecture Series which, after twenty-five years, is one of the most popular public lecture series at the University of Cambridge. The risk lectures in 2010 were amongst the most popular yet and, in essay form, they make for a lively and engaging read for specialists and non-specialists alike.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Risk perception; Risk assessment